CHRISTIAN MISSION AS NEW LIFE IN JESUS - Kalliath, Antony (Asian Horizons, 2011)
What is enthralling and absorbing while journeying through the narrative of the Bible is its bewildering array of literary trajectories, and its genre of authors. It is a mystifying anthology of poems, parables, psalms, discourses, stories, chronicle, laws, history, etc. Its authors richly range from historians, judges, Levites, kings, priests, theologians to prophets, seers, and saints. Even Yahweh ingeniously scripts his own autobiography as the Israelites take on their tryst with destiny through their intriguing history. The history of the Bible is exuberantly choreographed by its wide diversity of authors, themes, literary styles, and ever changing geography and the evolutionary historiography. Indeed, any valid exegetical study of the Bible should take into consideration the unity of the whole of Scripture along with the living tradition of the Church and the analogy of faith.1 All these three norms can be brought together in a neat harmony on two accounts: its undergirding theme of Life and an ever engaging God of Life.